The home jar : stories - Zafris, Nancy (Switchgrass Books, 2013)
"Zafris is a critically acclaimed writer because of the highly distinctive, piercing intelligence that underlies her works. This book gathers some of her short stories that are laugh-out-loud funny one moment and bittersweet the next"--